COLLABORATION WITH PENTAHELIX MODEL IN DEVELOPING KAJOETANGAN HERITAGE TOURISM IN MALANG CITY - Wahida, Siti Nurul; Syafrieyana, Yana; Sukmana, Oman (Journal of Local Government Issues (logos), 2020)
This study aims to reveal the development of Kajoetangan Heritage as a tourist attraction site in the city of Malang. The researchers use the Pentahelix model to look at the development. The involvement of pentahelix stakeholders (government, community, private sector, academics, and media) is intended to develop the tourism site thoroughly. So far, the main problem behind the less optimal management of Kajoetangan Heritage Tourism is the lack of development of accessibility, facilities, and infrastructure. This research uses descriptive qualitative method while the data were collected through observation, interviews, and documentation. The results show that the collaboration between the Kajoetangan community, Malang heritage community, Department of Culture and Tourism of Malang, Soak Ngalam business, City Guide FM, and Intitute of National Technology Malang had succeeded in increasing the promotion of the Kajoetangan Heritage. However, the collaboration had not been able to contribute maximally to the regional income. This happens because the problems of accessibility, facilities, and infrastructure were not resolved and there was a weak capacity of the actors involved.